Grain boundary phase-containing samarium iron-based rare earth permanent magnet material, its manufacturing method, and applications

A samarium iron-based rare earth permanent magnet material with a controlled grain boundary phase, produced via rapid solidification and melt-spinning, addresses the challenge of uniform phase formation, enhancing coercive force and enabling cost-effective large-scale production.

JP2025501432AActive Publication Date: 2025-01-22NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024513242
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-11-22
Filing Date
2023-04-03
Publication Date
2025-01-22
Estimated Expiration
2043-04-03

AI Technical Summary

Technical Problem

Samarium iron-based rare earth permanent magnet materials face challenges in forming a continuous and uniform nonmagnetic grain boundary phase, leading to a large difference between actual and theoretical coercive force, and are difficult to produce on a large scale.

Method used

A samarium iron-based rare earth permanent magnet material with a grain boundary phase, formulated as Sm a Fe b Co c Ti d M e, where M is B, C, Al, or Si, and produced through rapid solidification and melt-spinning, controlling parameters like melt temperature, pressure difference, and solidification speed to achieve a uniform grain boundary phase.

Benefits of technology

The solution results in a quenched ribbon with improved coercive force and uniform grain boundary phase, suitable for low-cost large-scale production of high-performance magnets.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025501432000001_ABST
    Figure 2025501432000001_ABST
Patent Text Reader

Abstract

The present invention provides a method for producing a samarium-iron-based rare earth permanent magnet material containing grain boundary phase, and by controlling the alloy components and the process parameters in the rapid solidification method, the problem of the inability to form a non-magnetic grain boundary phase due to the lack of liquid phase in the samarium-iron-based rare earth permanent magnet material can be solved, and the purity of the main phase can be improved. This method includes: using pure metal samarium, iron, cobalt, titanium and other key elements as raw materials, and preparing the raw materials by converting the ratio of the atomic number of the pure metal into the mass ratio; using a vacuum high-frequency induction melting furnace to melt the alloy under the condition of high purity argon gas to obtain a master alloy ingot of nominal composition, and melting the alloy twice to keep the sample uniform; grinding the surface impurities of the alloy ingot, crushing it into small pieces, and putting it into a vacuum rapid solidification device, and controlling the rapid solidification speed to 5m / s to 50m / s to obtain a uniform and stable rapid ribbon-shaped samarium-iron-based rare earth permanent magnet containing grain boundary phase. The quenched ribbon-like thin film produced in the present invention has excellent performance at low cost and can be widely applied in the fields of electronic information, energy conversion, etc.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims priority from Application No. 202211464706.4, filed with the State Intellectual Property Office of China on November 22, 2022, entitled "Grain boundary phase-containing samarium iron-based rare earth permanent magnet material, its manufacturing method, and application," the entire contents of which are incorporated herein by reference.

[0002] The present invention relates to the technical field of rare earth permanent magnet materials, and in particular to a grain boundary phase-containing samarium iron-based rare earth permanent magnet material, a manufacturing method thereof, and applications thereof. [Background technology]

[0003] Samarium iron-based rare earth permanent magnet materials were discovered in the 1980s, and have been developed for 40 years. With the rising price of rare earths in the current international market and the rapid development of China's new energy automobile industry, the demand for rare earth permanent magnet materials is expanding, which urges the development of permanent magnets with low rare earth content and high magnetic energy product. Samarium iron-based permanent magnet materials have the lowest rare earth element content, low cost, high anisotropy magnetic field, high saturation magnetization strength, and higher theoretical magnetic energy product, and their Curie temperature can reach above 500℃, making them suitable for use in high temperature magnetic materials.

[0004] At present, there are three main methods for producing samarium iron-based rare earth permanent magnet materials: sintering, redox and rapid solidification. The sintering method usually involves melting pure metal elements into an alloy ingot, then grinding the ingot into micron-sized powder, and then sintering the micron-sized powder into a block-shaped magnet through orientation molding and pressing. However, this method has a slow cooling rate, and the crystal grain size of the resulting magnet is generally large and the coercive force is low. The redox method involves reducing various raw oxide powders in a ball mill through high-energy ball milling to produce alloy powder, but this method is not suitable for large-scale production. Meanwhile, the rapid solidification method usually involves rapidly cooling to produce samarium iron-based rare earth permanent magnet materials with nanoscale crystal grains. This method is easy to operate and convenient for industrial production.

[0005] However, since samarium iron-based rare earth permanent magnet materials do not have a liquid phase in the phase region, it is difficult to form a continuous, uniform nonmagnetic grain boundary phase, and furthermore, there is a large difference between the actual coercivity and the theoretical coercivity. Researchers working with rare earth permanent magnet materials have hoped to construct a quenched ribbon of samarium iron-based rare earth permanent magnet in which the main phase is surrounded by a nonmagnetic grain boundary phase, but this has also been one of the hot topics in the field of magnet materials research in recent years. Summary of the Invention [Problem to be solved by the invention]

[0006] In view of the above circumstances, the present invention aims to provide a grain boundary phase-containing samarium iron based rare earth permanent magnet material, a manufacturing method thereof, and applications thereof. The grain boundary phase-containing samarium iron based rare earth permanent magnet material provided by the present invention has a grain boundary phase and has better performance. [Means for solving the problem]

[0007] The present invention provides a grain boundary phase-containing samarium iron-based rare earth permanent magnet material, the chemical formula of which is: Sm a Fe b Co c Tid M e Formula I and In formula I, 0.5≦a≦1.5, 7.5≦b≦9.0, 2.0≦c≦3.0, 0.5≦d≦1.5, and 0.1≦e≦2.0; M is one or more selected from the group consisting of B, C, Al and Si.

[0008] Preferably, the grain boundary phase-containing samarium iron based rare earth permanent magnet material contains a samarium iron based main phase, a grain boundary phase and an α-Fe phase, A non-magnetic element is segregated and distributed in the grain boundary phase, The grain boundary phase envelops the surface of the samarium-iron-based main phase.

[0009] Preferably, the volume content of the samarium-iron-based main phase in the grain boundary phase-containing samarium-iron-based rare earth permanent magnet material is 70% to 99%, The grain boundary phase in the grain boundary phase-containing samarium iron-based rare earth permanent magnet material has a volume content of 1% to 30%; The volume content of the α-Fe phase in the grain boundary phase-containing samarium iron-based rare earth permanent magnet material is 1% to 20%.

[0010] Preferably, the crystal grain size of the samarium-iron-based main phase is 20 nm to 500 nm, The grain size of the grain boundary phase is 1 nm to 50 nm.

[0011] The present invention provides a method for producing the grain boundary phase-containing samarium iron-based rare earth permanent magnet material described in the above technical solution, preparing alloy raw materials, melting them, and casting them to obtain a master alloy; and rapidly solidifying and melt spinning the master alloy to obtain a grain boundary phase-containing samarium iron-based rare earth permanent magnet material.

[0012] Preferably, the output of the smelting plant is 14 kW to 19 kW.

[0013] Preferably, the output of the casting is 5kw to 9kw.

[0014] Preferably, the nozzle diameter of the quartz tube during the rapid solidification and melt spinning is 1 mm to 4 mm, and the distance from the nozzle of the quartz tube to the copper roll is 1 mm to 4 mm.

[0015] Preferably, the melt temperature during the rapid solidification and melt spinning is 1000° C. to 1700° C., the pressure difference between the gas storage tank and the chamber is 0.02 MPa to 0.06 MPa, and the rapid solidification speed is 5 m / s to 50 m / s.

[0016] The present invention provides a magnetic device comprising the grain boundary phase-containing samarium iron-based rare earth permanent magnet material described in the above technical solution.

[0017] The present invention has found that the control of the alloy composition and the quenching solidification process has a great influence on the grain size and micro-morphology of the quenched ribbon sample, for example, the alloy composition, the quenching solidification rate, the pressure difference between the gas storage tank and the chamber, and the melt temperature all have a great influence on the uniformity and performance of the sample. Therefore, the control of these parameters is the key to obtaining a quenched ribbon of nanocrystalline samarium iron rare earth permanent magnet with uniform grain boundary phase, which is also a problem to be solved by those skilled in the art. In addition, the content of the alloy composition and the quenching solidification rate are the most important parameters in the quenching process, which are also the key to affecting the purity and phase composition of the main phase. The present invention has found that the alloy with the chemical formula Sm a Fe b Co c Ti d M e (wherein, 0.5≦a≦1.5, 7.5≦b≦9.0, 2.0≦c≦3.0, 0.5≦d≦1.5, 0.1≦e≦1.0), M is an important additive element, and it was discovered that by controlling the roll speed to 5 m / s to 40 m / s or less, a stable rapidly cooled ribbon-like thin strip of samarium iron rare earth permanent magnet can be obtained. [Brief description of the drawings]

[0018] [Figure 1]1 is a transmission electron microscope photograph of a quenched ribbon of a samarium-iron rare earth permanent magnet produced in Comparative Example 1 of the present invention. [Diagram 2] FIG. 2 is an element detection diagram of a quenched ribbon of a samarium-iron rare earth permanent magnet produced in Comparative Example 1 of the present invention. [Diagram 3] 1 is a transmission electron microscope photograph of a quenched ribbon of a grain boundary phase-containing samarium iron rare earth permanent magnet produced in Example 1 of the present invention. [Figure 4] FIG. 2 is an element detection diagram of the quenched ribbon of the grain boundary phase-containing samarium iron rare earth permanent magnet produced in Example 1 of the present invention. [Diagram 5] FIG. 2 is an XRD diffraction pattern of the quenched ribbon of the samarium-iron rare earth permanent magnet produced in Example 1 of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] The present invention provides a grain boundary phase-containing samarium iron-based rare earth permanent magnet material, the chemical formula of which is: Sm a Fe b Co c Ti d M e Formula I and In formula I, 0.5≦a≦1.5, 7.5≦b≦9.0, 2.0≦c≦3.0, 0.5≦d≦1.5, and 0.1≦e≦2.0; M is one or more selected from the group consisting of B, C, Al and Si.

[0020] In the present invention, the a is preferably 0.8 to 1.2, and more preferably 1; the b is preferably 8 to 8.5, and more preferably 8.2 to 8.3; the c is preferably 2.3 to 2.7, and more preferably 2.5; the d is preferably 0.8 to 1.2, and more preferably 1%; and the e is preferably 0.5 to 1.5, and more preferably 0.8 to 1.2, and most preferably 1%.

[0021] In the present invention, the grain boundary phase-containing samarium iron based rare earth permanent magnet material preferably contains a samarium iron (cobalt) substrate main phase, a grain boundary phase and an α-Fe phase.

[0022] In the present invention, preferably, the non-magnetic element is segregated and distributed mainly in the grain boundary phase, and the grain boundary phase uniformly surrounds the surface of the samarium-iron based main phase.

[0023] In the present invention, the volume content of the samarium-iron-based main phase in the grain boundary phase-containing samarium-iron-based rare earth permanent magnet material is preferably 70% to 99%, more preferably 75% to 95%, more preferably 80% to 90%, and most preferably 85%. The volume content of the grain boundary phase in the grain boundary phase-containing samarium-iron-based rare earth permanent magnet material is preferably 1% to 30%, more preferably 5% to 25%, more preferably 10% to 20%, and most preferably 15%. The volume content of the α-Fe phase (soft magnetic phase) in the grain boundary phase-containing samarium-iron-based rare earth permanent magnet material is preferably 1% to 20%, more preferably 5% to 15%, more preferably 8% to 12%, and most preferably 10%.

[0024] In the present invention, the crystal grain size of the samarium-iron-based main phase is preferably 20 nm to 200 nm, more preferably 50 nm to 150 nm, more preferably 80 nm to 120 nm, and most preferably 100 nm, and the crystal grain size of the grain boundary phase is preferably 2 nm to 100 nm, more preferably 10 nm to 80 nm, more preferably 20 nm to 60 nm, more preferably 30 nm to 50 nm, and most preferably 40 nm.

[0025] The present invention provides a method for producing the grain boundary phase-containing samarium iron-based rare earth permanent magnet material described in the above technical solution, A master alloy is obtained by blending raw alloys, melting them, and casting them. and rapidly solidifying and melt spinning the master alloy to obtain a grain boundary phase-containing samarium iron-based rare earth permanent magnet material.

[0026] In the present invention, there is no particular limitation on the alloy raw materials, and any raw materials for producing a permanent magnet material that are well known to those skilled in the art can be used. In the present invention, it is sufficient to provide a Sm source, an Fe source, a Co source, a Ti source, and an M source.

[0027] In the present invention, there is no particular limitation on the method of preparing the raw materials, and the raw materials may be prepared according to the chemical formula of Formula I using a method well known to those skilled in the art. When preparing the raw materials, it is preferable to replenish the burnt amount, and the burnt element is Sm, that is, when preparing the Sm element, it is added in an amount of 1 wt% to 30 wt%, more preferably 5% to 25%, more preferably 10% to 20%, and most preferably 15%.

[0028] In the present invention, the melting is preferably carried out using a vacuum high-frequency induction furnace, and the degree of vacuum during the melting process is (3 to 7) × 10 -2 Pa is preferably (4 to 6) × 10 -2 Pa is more preferable, and 5×10 -2 It is preferable that the melting power is 14kW to 19kW, more preferably 15kW to 18kW, and most preferably 16kW to 17kW, the casting power is preferably 5kW to 9kW, more preferably 6kW to 8kW, and most preferably 7kW, the number of times of melting is preferably 1 to 3, and it is more preferable that the alloy is repeatedly melted twice.

[0029] In the present invention, preferably, the melting and casting method comprises the steps of: The alloy that is the raw material is placed in a vacuum induction melting furnace, and after charging, the furnace lid is closed and (3~7) x 10 -2It is preferable that the method includes drawing a vacuum to 100 Pa, baking at a relatively low temperature to remove water vapor and gas adsorbed on the surface of the raw materials, filling with high purity argon gas after the vacuum level has stabilized, gradually increasing the heating output, reducing the heating output after the raw materials have completely melted, keeping the temperature for 2 to 5 minutes, and then casting the alloy liquid into a copper mold and cooling it.

[0030] In the present invention, the relatively low temperature is preferably 1400° C. to 1800° C., more preferably 1500° C. to 1700° C., and most preferably 1600° C. After the vacuum is stabilized, the degree of vacuum is <2×10 -2 The pressure of the filled argon gas is preferably 0.04 MPa to 0.08 MPa, more preferably 0.05 MPa to 0.07 MPa, and most preferably 0.06 MPa. The purity of the argon gas is preferably 99.999%. The range of the gradually increasing output is preferably 12 kW to 18 kW, more preferably 13 kW to 17 kW, more preferably 14 kW to 16 kW, and most preferably 15 kW. The range of the decreasing heating output is preferably 10 kW to 8 kW, and more preferably 9 kW. The warming time is preferably 3 to 4 minutes.

[0031] In the present invention, it is preferable to polish impurities on the surface of the master alloy and to break the master alloy into small pieces before the rapid solidification and melt spinning. The rapid solidification and melt spinning are preferably performed in a vacuum rapid solidification apparatus, and a rapidly quenched ribbon of rare earth containing grain boundary phase can be discharged from the vacuum rapid solidification apparatus.

[0032] In the present invention, the nozzle diameter of the quartz tube during the rapid solidification and melt spinning is preferably 1 mm to 4 mm, more preferably 2 mm to 3 mm. The distance from the nozzle of the quartz tube to the copper roll is preferably 1 mm to 4 mm, more preferably 2 mm to 3 mm. The melt temperature is preferably 1000°C to 1700°C, more preferably 1100°C to 1600°C, more preferably 1200°C to 1500°C, and most preferably 1300°C to 1400°C. The melt temperature is preferably measured using an infrared thermometer. The pressure difference between the gas storage tank and the chamber is preferably 0.02 MPa to 0.06 MPa, more preferably 0.03 MPa to 0.05 MPa, and most preferably 0.04 MPa. The rapid solidification speed is preferably 10 m / s to 50 m / s, more preferably 20 m / s to 40 m / s, and most preferably 30 m / s.

[0033] The present invention provides a magnetic device comprising the grain boundary phase-containing samarium iron-based rare earth permanent magnet material described in the above technical solution.

[0034] The rapidly spun ribbon produced by the present invention is low-cost and can be used in the development of bonded magnetic powders and magnetic devices in fields such as information and communications. Compared to conventional techniques, it overcomes problems in samarium-iron-based rare earth permanent magnet materials, such as a lack of grain boundary phase and ease of α-Fe precipitation, and provides a new concept for the development of new samarium-iron-based rare earth permanent magnet bodies with high coercivity.

[0035] The microstructure of the grain boundary phase-containing samarium iron-based rare earth permanent magnet material provided by the present invention contains not only a samarium iron-based main phase having permanent magnetic properties, but also a grain boundary phase, which is not present in conventional samarium iron-based rare earth permanent magnet materials. The present invention utilizes the samarium iron-based main phase and the grain boundary phase to achieve high magnetic properties, does not require complicated processes, and can be applied to low-cost rare earth permanent magnet materials. EXAMPLES

[0036] Example 1 Raw material mixture: Stoichiometric formula (SmFe 8.8 Co2.2 Ti1B 0.25 The raw materials are mixed in the following molar ratio of each element:

[0037] Melting: Put the mixed raw materials into a vacuum induction melting furnace, cover the furnace after charging, and mix 5×10 -2 The material is then evacuated to a vacuum of 10 Pa, and then baked at a lower temperature to remove water vapor and gas adsorbed on the surface of the material. After the vacuum level stabilizes (<2×10 -2 The furnace was filled with high-purity argon gas (99.999%) at 0.06 MPa and the heating power was gradually increased to 16.8 kW. After the raw materials were completely melted, the heating power was reduced to 8 kW and the temperature was maintained for 2 to 5 minutes. The molten steel was then cast and cooled in a copper mold to obtain a master alloy.

[0038] After the surface impurities of the above-obtained mother alloy are polished, the mother alloy is pulverized and filled into a quartz tube. The nozzle diameter of the quartz tube is 1 mm, the distance from the nozzle of the quartz tube to the copper roll is 3 mm, and the mother alloy is melted in a vacuum high-frequency induction melting furnace. The melt temperature measured by an infrared thermometer is 1600°C, the pressure difference between the gas storage tank and the chamber is 0.04 MPa, and the ribbon is discharged at a quenching solidification speed of 25 m / s to obtain a quenched ribbon-like ribbon of a rare earth permanent magnet containing a uniform and stable grain boundary phase.

[0039] FIG. 3 shows a transmission electron microscope photograph of the microstructure of the grain boundary phase-containing samarium iron-based permanent magnet material produced in Example 1 of the present invention. As can be seen from FIG. 3, the microstructure of the grain boundary phase-containing samarium iron-based permanent magnet material is mainly composed of a samarium iron-based main phase and a grain boundary phase, the grain boundary phase is distributed along the grain boundaries, the crystal grain size of the main phase is 100 nm to 200 nm, and the size of the grain boundary phase is 3 nm to 30 nm.

[0040] FIG. 4 shows the test results of the element distribution of the grain boundary phase-containing samarium iron-based rare earth permanent magnet material produced in Example 1, and it can be seen that the Ti element is mainly segregated in the grain boundary phase.

[0041] FIG. 5 is an XRD diffraction pattern of the quenched ribbon of the samarium-iron rare earth permanent magnet produced in Example 1 of the present invention. As can be seen from FIG. 5, the ratio of the main phase ThMn12 to the soft magnetic phase α-Fe is 97.58 wt.%:2.42 wt.%.

[0042] Example 2 Stoichiometric formula Sm1Fe 8.8 Co 2.2 Ti1B 0.5 A grain boundary phase-containing samarium-iron-based permanent magnet material was produced in the same manner as in Example 1, except that the raw materials were mixed in the above molar ratio of each element.

[0043] Example 3 Stoichiometric formula Sm1Fe 8.8 Co 2.2 A grain boundary phase-containing samarium-iron-based permanent magnet material was produced in the same manner as in Example 1, except that the raw materials were mixed in a molar ratio of each element of Ti1B1.

[0044] Example 4 A samarium-iron-based permanent magnet material containing a grain boundary phase was produced in the same manner as in Example 1, except that the rapid solidification / melt spinning speed was 40 m / s.

[0045] Example 5 Stoichiometric formula Sm1Fe 8.8 Co 2.2 Ti1B 0.5 The raw materials were mixed in the above molar ratio of each element, and a grain boundary phase-containing samarium-iron-based permanent magnet material was produced in the same manner as in Example 1, except that the rapid solidification and melt spinning speed was 40 m / s.

[0046] Example 6 Stoichiometric formula Sm1Fe 8.8 Co 2.2 Ti1B 0.75 The raw materials were mixed in the above molar ratio of each element, and a grain boundary phase-containing samarium-iron-based permanent magnet material was produced in the same manner as in Example 1, except that the rapid solidification and melt spinning speed was 40 m / s.

[0047] Example 7 Stoichiometric formula Sm1Fe8.8 Co 2.2 A grain boundary phase-containing samarium-iron-based permanent magnet material was produced in the same manner as in Example 1, except that the raw materials were mixed in a molar ratio of Ti1B1 and the rapid solidification and melt spinning speed was 40 m / s.

[0048] Comparative Example 1 Raw material mixture: Stoichiometric formula (SmFe 8.8 Co 2.2 The raw materials were mixed in the following molar ratios for each element:

[0049] Melting: Put the mixed raw materials into a vacuum induction melting furnace, cover the furnace after charging, and mix 5×10 -2 The material is then evacuated to a vacuum of 10 Pa, and then baked at a relatively low temperature to remove water vapor and gas adsorbed on the surface of the material. After the vacuum level stabilizes (<2×10 -2 The furnace was filled with high-purity argon gas (99.999%) at 0.06 MPa and the heating power was gradually increased to 15.7 kW. After the raw materials were completely melted, the heating power was reduced to 7.6 kW and the temperature was maintained for 2 to 5 minutes. The molten steel was then cast and cooled in a copper mold to obtain a master alloy.

[0050] The above-obtained master alloy was ground to remove surface impurities, and then packed into a quartz tube. The nozzle diameter of the quartz tube was 1 mm, and the distance from the nozzle of the quartz tube to the copper roll was 3 mm. The master alloy was melted in a vacuum high-frequency induction melting furnace. The melt temperature measured by an infrared thermometer was 1550°C, the pressure difference between the gas storage tank and the chamber was 0.04 MPa, and the ribbon was discharged at a rapid solidification speed of 25 m / s to obtain a uniform and stable rapid-cooled ribbon-shaped ribbon of a rare earth permanent magnet containing grain boundary phase.

[0051] Fig. 1 is a transmission electron microscope test image of a quenched ribbon of a samarium iron rare earth permanent magnet produced in Comparative Example 1 of the present invention. Fig. 2 is an element detection image of the quenched ribbon of a samarium iron rare earth permanent magnet produced in Comparative Example 1 of the present invention. As can be seen from Figs. 1 and 2, no grain boundary phase was observed in the alloy to which the M element was not added.

[0052] The magnetic properties of the products manufactured in the examples and comparative examples of the present invention are measured. The measurement method is to measure the hysteresis loop by applying an external magnetic field under vacuum conditions of a magnetic field of 9 T in a vacuum (apparatus type: PPMS-EverCool).

[0053] The measurement results are as follows:

[0054] [Table 1]

[0055] In Examples 1 to 7, it was found that the addition of the key M element and the corresponding manufacturing process caused the precipitation of grain boundary phases that uniformly enclose the crystals of the samarium-iron-based main phase in the samarium-iron-based permanent magnet material, and that the coercivity of the quenched ribbon manufactured in Example 1 was significantly increased compared to Comparative Example 1.

[0056] It should be pointed out that the above description is only a preferred embodiment of the present invention, and those skilled in the art may make some improvements and modifications without departing from the principle of the present invention, and these improvements and modifications should also be regarded as within the protection scope of the present invention.

Claims

1. The chemical formula is: Sm a Fe b Co c Ti d M e Formula I The present invention relates to a grain boundary phase-containing samarium iron-based rare earth permanent magnet material. (In formula I, 0.5≦a≦1.5, 7.5≦b≦9.0, 2.0≦c≦3.0, 0.5≦d≦1.5, and 0.1≦e≦2.0, M is one or more selected from the group consisting of B, C, Al and Si.

2. the grain boundary phase-containing samarium-iron-based rare earth permanent magnet material comprises a samarium-iron-based main phase, a grain boundary phase, and an α-Fe phase, A non-magnetic element is segregated and distributed in the grain boundary phase, 2. The samarium-iron-based rare earth permanent magnet material containing grain boundary phase according to claim 1, wherein the grain boundary phase envelops a surface of the samarium-iron-based main phase.

3. the volume content of the samarium-iron-based main phase in the grain boundary phase-containing samarium-iron-based rare earth permanent magnet material is 70% to 99%; the grain boundary phase has a volume content of 1% to 30% in the grain boundary phase-containing samarium iron-based rare earth permanent magnet material, The grain boundary phase-containing samarium iron based rare earth permanent magnet material according to claim 2, characterized in that the volume content of the α-Fe phase in the grain boundary phase-containing samarium iron based rare earth permanent magnet material is 1% to 20%.

4. The crystal grain size of the samarium-iron-based main phase is 20 nm to 500 nm, 3. The samarium-iron-based rare earth permanent magnet material containing grain boundary phase according to claim 2, characterized in that the grain size of the grain boundary phase is 1 nm to 50 nm.

5. A method for producing the grain boundary phase-containing samarium iron-based rare earth permanent magnet material according to claim 1, comprising the steps of: A master alloy is obtained by blending raw alloys, melting them, and casting them. and rapidly solidifying and melt spinning the master alloy to obtain a grain boundary phase-containing samarium iron-based rare earth permanent magnet material.

6. The method according to claim 5, characterized in that the power of the smelting is 14 kW to 19 kW.

7. The method according to claim 5, characterized in that the power of the casting is between 5 kW and 9 kW.

8. The method according to claim 5, characterized in that the nozzle diameter of the quartz tube during the rapid solidification and melt spinning is 1 mm to 4 mm, and the distance from the nozzle of the quartz tube to the copper roll is 1 mm to 4 mm.

9. The method according to claim 5, characterized in that the melt temperature during the rapid solidification and melt spinning is 1000°C to 1700°C, the pressure difference between the gas storage tank and the chamber is 0.02MPa to 0.06MPa, and the rapid solidification speed is 5m / s to 50m / s.

10. A magnetic device comprising the grain boundary phase-containing samarium iron-based rare earth permanent magnet material according to claim 1.

Citation Information

Patent Citations

  • Samarium-Containing Soft Magnetic Alloys

    CN109321784A

  • Magnet alloy containing rare earth element and permanent magnet containing rare earth element

    JP1992308062A

  • Iron-rare earth permanent magnet material and its production

    JP1993065603A

  • Method for producing rapid-cooled alloy

    JP2003320442A

  • Magnetic compound and manufacturing method therefor

    JP2017057471A